On the compatibility of high mass loading bismuth anodes for full-cell sodium-ion batteries. Issue 44 (28th October 2022) - Colbin, Lars Olow Simon; Nwafornso, Tochukwu E.; Li, Yunjie; Younesi, Reza
Abstract : The rate capability and cyclability of high mass loading metallic bismuth anodes are studied in full-cell sodium-ion batteries, using Prussian white cathodes. Abstract : Metallic bismuth is here studied as an anode material for sodium-ion batteries. The details of electrochemical redox reactions, rate performance and cycled life were investigated using relatively high mass loading electrodes in two- and three-electrode full-cells. It demonstrated that the rate capability of bismuth anodes with high mass loading are not as good as indicated in previous literatures where low mass loading electrodes were used. It also indicated that the resistances causing a faltering rate performance may be connected to a loss in particle contact during desodiation. Efforts were also made to study the different electrochemical processes that occur during early cycles. Less advantageous characteristics of bismuth electrodes are also discussed. For example, several different electrolyte solutions were tested for compatibility with the bismuth system, where only glyme-based solutions seemed to facilitate robust cycling.